PEMANFAATAN EKSTRAK DAUN MIMBA (Azadirachta indica) SEBAGAI PESTISIDA NABATI DALAM MENANGGULANGI HAMA ULAT BUAH (Helicoverpa armigera) PADA TANAMAN TOMAT (Solanum lycopersicum) - Maria Sri kartika Nona mina; Julianus Jeksen; Yovita Yasintha Bolly (Fakultas Pertanian Universitas Ratu Samban, 2025)
Tomato fruit caterpillar pests (Helicoverpa armigera) are one of the main factors that cause demage to tomato plantas, so that they can reduce crop producitivity. This study aims to test the effectiveness of botanical pesticides based on neem leaves (Azadirichta indica) as an environmentally friendly alternative pest control and compare it with chemical pesticides. This study was conducted with several treatments of neem leaf exract concentration, namely 40%, as well as controls and chemical pesticides as a comparison. The results of the study showed that the neem leaf botanical pesticide was able to siginificantly reduce the population of tomato fruit caterpillar pests. The effectiveness of control increased along with the concentration of the solution, where at a concentration of 40% the effectiveness reached 80%. The level of fruit damage also decreased by 40%. Chemical pesticides showed higher effectiveness (90%) with a fruit damage level of only 20%. Although chemical pesticides are more effective, the botanical pesticide neem leaves offer an environmentally friendly solution with a lower risk of chemical residues. Thus, neem leaves can be an alternative for farmers to reduce dependence on chemical pesticides, especially on a sustainable agricultural scale.